A phytosociological study of a sand dune in La Paz, Laoag City - Co, Corazon C. 1943-
The purpose of this study was to make a quantitative analysis of vegetation of a dune slope in La Paz, Laoag City, in order to determine the organization of the community in terms of plant community types, and the probable development of the community and its implications on man-initiated attempts to stabilize a sand dune.